Chemical, genetic and structural assessment of pyridoxal kinase as a drug target in the African trypanosome - Jones, Deuan C (Blackwell Publishing Ltd, 2012)
Pyridoxal-5′-phosphate (vitamin B(6)) is an essential cofactor for many important enzymatic reactions such as transamination and decarboxylation. African trypanosomes are unable to synthesise vitamin B(6)de novo and rely on uptake of B(6) vitamers such as pyridoxal and pyridoxamine from their hosts, which are subsequently phosphorylated by pyridoxal kinase (PdxK). A conditional null mutant of PdxK was generated in Trypanosoma brucei bloodstream forms showing that this enzyme is essential for growth of the parasite in vitro and for infectivity in mice. Activity of recombinant T. brucei PdxK was comparable to previously published work having a specific activity of 327 ± 13 mU mg(−1) and a K(m)(app) with respect to pyridoxal of 29.6 ± 3.9 µM. A coupled assay was developed demonstrating that the enzyme has equivalent catalytic efficiency with pyridoxal, pyridoxamine and pyridoxine, and that ginkgotoxin is an effective pseudo substrate. A high resolution structure of PdxK in complex with ATP revealed important structural differences with the human enzyme. These findings suggest that pyridoxal kinase is an essential and druggable target that could lead to much needed alternative treatments for this devastating disease.